2023
DOI: 10.1039/d2ra06678e
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and self-assembly of ionic (PNIPAM-co-VIM) microgels and their adsorption property for phosphate ions

Abstract: The ionic P(NIPAM-co-VIM) microgels were prepared by a two-step method, and used as functional coating on Quartz Crystal Microbalance (QCM) sensor for the detection of trace phosphate ions in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The extensively developed metal-directed self-assembly has evolved as an elegant and efficient strategy for the controllable bottom-up construction of well-defined supramolecular architectures, which are based on various noncovalent bonds, such as van der Waals, coordination, electrostatic, hydrogen, and halogen bonds. More recently, functional supramolecular assemblies have played critical roles in catalysis, biological simulations, molecular recognition, host–guest encapsulation, anion sensing, and functional materials because of their structural diversity and excellent physical properties. So far, all of these supramolecular assembled structures have been exquisitely designed since the 1990s for metal–organic/organometallic square macrocycles (“molecular squares”). , Recently, there has been strong interest in the design and function of molecular squares, and they are widely used in various fields, such as catalysis, luminescence, and anticancer therapy due to the interesting physical and chemical properties of these architectures. Among multidentate N-donor ligands, pyrazole ligands are often used in the self-assembly of polynuclear pyrazole-bridged ring structures with metal nodes via directional metal–ligand interactions. , In our previous studies, functional square-like metallamacrocycles were prepared via a directed self-assembly approach that exploited metal–ligand and metal–metal bonding interactions. These macrocyclic metal assemblies have displayed attr...…”
Section: Introductionmentioning
confidence: 99%
“…The extensively developed metal-directed self-assembly has evolved as an elegant and efficient strategy for the controllable bottom-up construction of well-defined supramolecular architectures, which are based on various noncovalent bonds, such as van der Waals, coordination, electrostatic, hydrogen, and halogen bonds. More recently, functional supramolecular assemblies have played critical roles in catalysis, biological simulations, molecular recognition, host–guest encapsulation, anion sensing, and functional materials because of their structural diversity and excellent physical properties. So far, all of these supramolecular assembled structures have been exquisitely designed since the 1990s for metal–organic/organometallic square macrocycles (“molecular squares”). , Recently, there has been strong interest in the design and function of molecular squares, and they are widely used in various fields, such as catalysis, luminescence, and anticancer therapy due to the interesting physical and chemical properties of these architectures. Among multidentate N-donor ligands, pyrazole ligands are often used in the self-assembly of polynuclear pyrazole-bridged ring structures with metal nodes via directional metal–ligand interactions. , In our previous studies, functional square-like metallamacrocycles were prepared via a directed self-assembly approach that exploited metal–ligand and metal–metal bonding interactions. These macrocyclic metal assemblies have displayed attr...…”
Section: Introductionmentioning
confidence: 99%
“…Some other pollutants such as uranium, 86 phosphate, 37 dichromate, arsenate, 87 and permanganate 88 ions, as well as various aromatic compounds such as bisphenols (bisphenol F (BPF), bisphenol E (BPE), bisphenol B (BPB) and bisphenol A (BPA)), 89 anthocyanins, 90 naphthalene and 1-naphthylamine, 91 and surfactants 92 can be effectively eliminated from aqueous solutions using different types of microgel adsorbents. Hydrogen, 93 methane, 83 and iodine 94 can also be separated by microgels through adsorption.…”
Section: Adsorptive Pollutant Removal By Microgels (Adsorbents)mentioning
confidence: 99%
“…Thus, the microgel adsorbed the maximum number of cationic pollutants due to its anionic structure and swelling state. Yang et al 37 reported the adsorption capacity of a cationic microgel system. Kyrey et al 107 and Naseem et al 81 also reported the preparation of microgels with and without comonomers, respectively, and their use as adsorbents for the removal of toxic pollutants.…”
Section: Classificationsmentioning
confidence: 99%
See 2 more Smart Citations